Influence of Albizia lebbeck Saponin and Its Fractions on In Vitro Gas Production Kinetics, Rumen Methanogenesis, and Rumen Fermentation Characteristics. (4th March 2014) - Sirohi, Sunil Kumar; Goel, Navneet; Singh, Nasib
Abstract : The present study was undertaken to investigate the effect of crude seed powder (CSP) and gross saponins extract (GSE) of seeds of Albizia lebbeck on antimicrobial activity by taking two Gram-positive ( Staphylococcus aureus and Bacillus cereus ), two Gram-negative ( Escherichia coli and Salmonella Typhi) bacteria, and two fungi species ( Aspergillus niger and Candida butyric ) were taken at 25, 50, 100, 250, and 500 µg levels using agar well diffusion method. Zone of inhibition was increased with increasing of concentration of CSP and saponins which indicates that Gram-negative bacteria ( E. coli ), Gram-positive bacteria ( B. cereus ), and A. niger were significantly susceptible to inhibition. Another experiment was conducted to study the effect of GSE and saponins fraction A and B of A. lebbeck supplementation at 6% on DM basis on methane production and other rumen fermentation parameters using in vitro gas production test, by taking three different type diets, that is, high fiber diet (D1, 60R : 40C), medium fiber diet (D2, 50R : 50C), and low fiber diet (D3, 40R : 60C). Significant (P ≤ 0.05 ) increase was seen in IVDMD, methane production; however ammonia nitrogen concentration decreased as compared to control. The methane production was reduced in a range between 12 and 49% by saponin supplemented diets except in case of GSE in D2. Sap A showed the highest methane reduction per 200 mg of truly digested substrate (TDS) than other treatment groups. Results in relation with quantification of methanogens and protozoa by qPCR indicated the decreasing trend with saponins of A. lebbek in comparison with control except total methanogen quantified using mcr-A based primer.